2011
DOI: 10.1021/la200223g
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Activated Micromixers for Separation Membranes

Abstract: Presented here is a radically novel approach to reduce concentration polarization and, potentially, also fouling by colloids present in aqueous feeds: magnetically responsive micromixing membranes. Hydrophilic polymer chains, poly(2-hydroxyethyl methacrylate) (PHEMA), were grafted via controlled surface-initiated atom transfer radical polymerization (SI-ATRP) on the surface of polyamide composite nanofiltration (NF) membranes and then end-capped with superparamagnetic iron oxide magnetite (Fe(3)O(4)) nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
91
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 26 publications
6
91
0
Order By: Relevance
“…Building upon this, an exciting new type of filtration membrane responsive to an external magnetic field was recently developed by our groups [5]. The nanofiltration behavior of these membranes can be altered without affecting the characteristics of the entire feedstream by generating small scale mixing above the membrane surface via the movement of grafted polymer chains in a magnetic field [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Building upon this, an exciting new type of filtration membrane responsive to an external magnetic field was recently developed by our groups [5]. The nanofiltration behavior of these membranes can be altered without affecting the characteristics of the entire feedstream by generating small scale mixing above the membrane surface via the movement of grafted polymer chains in a magnetic field [5].…”
Section: Introductionmentioning
confidence: 99%
“…The nanofiltration behavior of these membranes can be altered without affecting the characteristics of the entire feedstream by generating small scale mixing above the membrane surface via the movement of grafted polymer chains in a magnetic field [5]. In the presence of an oscillating magnetic field both rejection and flux increased for feed streams containing dissolved salts such as MgSO 4 and CaCl 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The superparamagnetic (Fe 3 O 4 ) nanoparticles were then attached to the polymer chain ends. As for membrane filtration, the modified magnetic responsive membranes operated under presence of an oscillating magnetic field manifested improvement of permeation (30% higher flux) and salt rejection (15% higher rejection of CaCl 2 ) than the membrane operated in the absence of an oscillating magnetic field [19].…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques have been explored to incorporate nanoparticles onto the membrane surface, including radical grafting [19,20], hydrogel coating [15], self-polymerization [18], and polyelectrolyte multilayer modification (PEM) [7]. Himstedt et al [19] and Yang et al [20] demonstrated the integration of magnetite nanoparticles on surface of polyamide nanofiltration (NF) membrane through surface-radical polymerization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation